La violence envers les Barbares et la figure de l’empereur chrétien : Zosime, Histoire nouvelle IV, 26 ; 30 ; 40. - Nastasia Fouillet (Cahiers des Études Anciennes)
Three passages from the 4th book of Zosimus’ New History enable us to study the irruption of a spontaneous form of violence against barbarians who are depicted as a danger for the Empire. The massacre of barbarians is accomplished by one or several members of the Roman army without the Emperor knowing it: the slaughter is presented as a legitimate response to this potential threat represented by the barbarians. The article looks at the causes of the emergence of violence as exposed by Zosimus, through an analyse of the characters, whether they are actors or victims of this violence, and focuses on the particular treatment of the figure of the Christian Emperor.